Interviewing Hugo Hamilton - Izarra, Laura P. Z.; Aquino, Patricia (ABEI Journal, 2013)
This interview took place at the Universidade de São Paulo, Brazil, on 19th August 2013. Hamilton discussed the relationship between language and identity and reflected upon the art of writing in his novel The SpeckledPeople which is part of the curriculum of the undergraduate course of Linguistic and Literary Studies in English.Keywords: Hugo Hamilton; The Speckcled People; language; identity; nation.